ANALYSIS OF FARMERS INCOME SELLING IN SUCO LOUR ZUMALAI ADMINISTRATIVE POST-COVALIMA MUNICIPALITY - Colo, Heribertos A.; Tilman, Maria; Martins, Aleixo (Ridwan Institute, 2025)
The research aims to analyze farmers' income selling Corn in Suco Lour, Zumalai Administrative Post, Covalima Municipality. The research employs descriptive methods, utilizing a simple random sampling technique to select a sample of 100 farmers from the population. The data collection involves three methods: interviews, which facilitate direct communication with the farming community; observation to witness farming activities firsthand; and questionnaires designed to gather structured information. The researcher analyzed with the results of counting through economic analysis equipment, responded with significant results as follows: (i) the total number of farmer family members responded in fifty (50), discovered farmers Secondary Education with its minimum frequency of two (2) people, 4 percent, discovered non-alphabetic farmers got the highest frequency of twenty-one (21) people, with 42%. (ii) The impact of technology on productivity: Investigate how the adoption of modern agricultural technologies influences corn production efficiency and income levels among farmers. The study highlights the factors influencing earnings, including production costs, market access, and pricing strategies. This research can inform policymakers and agricultural stakeholders about the economic challenges faced by local farmers, guiding the development of targeted interventions to enhance profitability and sustainability in the agricultural sector. Furthermore, the findings may serve as a basis for further studies on income diversification and agricultural practices in similar regions, ultimately contributing to improved livelihoods for farming communities.